Pengenalan dan Pelatihan Penggunaan Aplikasi Mendeley pada Santri Pondok Pesantren Al Munawwir Komplek L Krapyak Yogyakarta: Penelitian - Anisatul Mukaromah; Tiara Rahmadhani N; Muhimmatul Mahmuda; Elma Nafi’atul M; Sumarsono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
High-quality academic writing requires the ability to manage references efficiently, systematically, and in accordance with academic standards. However, based on a survey conducted, the santri (Islamic boarding school students) at Pondok Pesantren Al Munawwir Komplek L, Krapyak, Yogyakarta, still face various challenges in reference management, particularly in compiling bibliographies and citations. This issue highlights the need to improve digital literacy among santri, especially in relation to academic writing. In response to this need, a training program was held to introduce and teach the use of Mendeley, a reference management software that assists in collecting, storing, organizing, and generating citations and bibliographies in an automatic and structured manner. The program consisted of several stages: preparation, socialization, technical training, intensive mentoring, and final evaluation. The main objective of this training was to equip the santri with practical skills in using Mendeley as part of strengthening their academic competencies. The program’s success was measured through participant feedback and the results of an evaluative quiz. Based on the evaluation, the majority of santri demonstrated a significant improvement in understanding and were able to use Mendeley independently. It is hoped that this initiative will contribute positively to enhancing the quality of academic writing within the pesantren environment and foster a stronger academic culture among the santri.